Global human papilloma virus vaccine implementation: An update. Issue 6 (8th March 2018) - Sabeena, Sasidharanpillai; Bhat, Parvati V.; Kamath, Veena; Arunkumar, Govindakarnavar
Abstract: Human papillomavirus (HPV) infections continue to be one of the most common sexually transmitted infections worldwide. The oncogenic potential of this virus was well established in anogenital malignancies and oropharyngeal cancers. Even though a fall in cervical cancer rates has been reported worldwide, the subsequent rise in HPV‐associated head and neck cancers among men and women have been reported from developed countries, necessitating the vaccination of adolescent boys as well. The objective of this narrative review is to provide an update on the current status of HPV vaccination worldwide. This will be helpful for clinicians in counseling parents and guardians as this vaccine mainly targets sexually naïve preadolescents. An electronic search of the databases was carried out to retrieve information concerning HPV vaccine implementation between July 2006 and 2017, with special emphasis on the current viewpoints, controversies and ethical issues. Globally, 74 countries have implemented the HPV vaccine in the national immunization schedule, and this vaccine is listed as an essential medicine by WHO. About 60% of the low‐ and lower–middle‐income countries have implemented the vaccine with financial assistance from Gavi and WHO. The HPV vaccine is a safe vaccine with no serious adverse effects as per the data available from developed nations as well as low/ lower middle/ upper middle‐income countries. However, long‐term follow‐up is essential to substantiate the impact of the vaccination programs in cancer prevention.